The Influence of Trust in Fintech and Perceived Security on the Decision to Use E-Wallets among Students in Mataram City - Febbyola Tri Lestari; Siti Aisyah Hidayati; I Gusti Agung Arista Pradnyani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of fintech, particularly e-wallets, is driving financial inclusion amidst increasing cybersecurity risks, but trust in fintech and perceived security are major barriers to adoption among university students. This study aims to analyze the influence of trust in fintech and perceived security on e-wallet adoption decisions among university students in Mataram City. Using an associative quantitative approach, data were collected through a Likert-scale questionnaire from a population of active e-wallet users, with a sample of 100 respondents determined using the Lemeshow formula and simple random sampling. The instrument was validated through factor analysis (KMO >0.6) and reliability (Cronbach's Alpha >0.7), and analyzed using SPSS 26 multiple linear regression after classical assumption testing. The results showed that trust in fintech (β=0.312, p=0.000) and perceived security (β=0.285, p=0.000) had a significant positive effect on adoption decisions (R²=61.2%). In conclusion, both variables explain adoption substantially, with trust being more dominant, recommending increased transparency and anti-phishing features for providers.